1996
DOI: 10.1007/bf02550853
|View full text |Cite
|
Sign up to set email alerts
|

Is general anaesthesia necessary for URS in women?

Abstract: A total of 65 women with ureteral stone who underwent ureteroscopy were divided randomly into two groups between April 1993 and March 1994. URS was performed under general anaesthesia in the first group (35 patients), and under local anaesthesia with sedation analgesia in the second group (30 patients). Only 2 patients of the second group did not tolerate the operation. The success rate was 88% in the first group and 83.3% in the second. There was no significant difference between the two groups. Since URS und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
1
13
0
2
Order By: Relevance
“…Yalçinkaya et al reported a success rate of 83% in their series with local ureteroscopic lithotripsy [3]. A similar success rate (88%) was reported by Abdel-Razzak et al [5].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Yalçinkaya et al reported a success rate of 83% in their series with local ureteroscopic lithotripsy [3]. A similar success rate (88%) was reported by Abdel-Razzak et al [5].…”
Section: Discussionsupporting
confidence: 69%
“…Several reports have shown the effectiveness of local ureteroscopic lithotripsy [3,4]. The review of a published series on treatment with ureteroscopy using multiple types of ureteroscopes and intracorporeal lithotripsy devices reveals success rates ranging from 86 to 100% [14][15][16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Während sich dies in zahlreichen ausländischen Veröffentlichungen widerspiegelt, in denen die URS als ambulanter Eingriff, in Analgosedierung, in Lokalanästhesie, für Kelchsteine, bei multimorbiden adipösen Patienten, bei Kindern und selbst in der Schwangerschaft untersucht wurde [4,5,6,7,8,22,26,38,39,40], hat die deutsche Gesetzgebung bis zur Einführung der DRGs durch die Finanzierung über die Liegedauer solche Entwicklungen nicht in gleichem Maße gefördert. Deshalb ist es nicht verwunderlich, dass es zur URS in Analgosedierung nur wenige deutsche Veröffentlichungen gibt.…”
Section: Ureterorenoskopieunclassified
“…Yalcinkaya ureteroskopierte 1996 ausschließlich Frauen in Sedoanalgesie und musste nur noch in 2 von 30 Fällen wegen unzureichender Analgesie zur Vollnarkose wechseln (6,7%) [38]. Auch Hosking [17] konnte den deutlichen Unterschied des Schmerzniveaus während der URS zwischen Männern und Frauen zeigen: seine Versagerquote für die Sedoanalgesie lag 1996 bei männlichen Patienten mit 27,8% (10/36) über 4-mal hö-her als die der weiblichen Patienten mit 6,3% (2/32), während in der vorliegenden Remifentanil-Studie die Quote auf 2,9% (4/140) gesamt und 0% (0/57) bei Frauen gesenkt werden konnte.…”
Section: Abb 6 ▲ Vergleich Der Schmerzangaben Von Männern Und Frauenunclassified